Report on practice in industry training in fish preservation. - Misa, Carmen A. (College of Fisheries, University of the Philippines, 1959)
As a prerequisite for graduation, students of the college of fisheries, university of the Philippines who have completed the two years academic training are required totake an apprenticeship for a period of four months. This is the period which prepares the students to put into actual practice whatever they have learned in the classrrom. This report includes all the observations and actual laboratories undertaken by the author. To all who helped this report I extend m heartfelt gratyitude especially to Prof. Nazario A. Pidlaon, Directo of the college of fisheries;Prof. Augusto D. Manalo, head of fisheries technology department for his advice and to Mrs. Honorata Magleo-Ferrer in her competent instructions in completing this report. Lastly, I am very grateful to my beloved parents, sisters and brothers who have sacrificed much in my studies.